Clinical Outcome of Dorsal Cervical C1–C2 Fusion Using C1 Lateral Mass Screws, C2 Lamina Screws, and Interarcual Bone Graft Technique - Tosic, Lazar; Baschera, Dominik; Oberle, Joachim; Golubovic, Jagos; Alfieri, Alex (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Aims To evaluate the clinical and radiologic results of patients treated with dorsal cervical C1–C2 fusion using C1 lateral mass screws, C2 lamina screws, and interarcual bone graft.Methods We retrospectively analyzed the clinical and radiologic results of eight patients treated from 2011 to 2016. Neck pain, neurologic deficits, use of analgesics, vertebral artery injury, C2 root injury, radiologic fusion rate, malposition of screws, and implant failure were examined on day 3 and at 3 and 12 months postoperatively.Results One patient required revision surgery for a right-sided medial cutout of a lamina screw. None of the patients had vascular or neurologic complications. All patients were pain free and had ceased all analgesic therapy at the first follow-up examination. At the 1-year follow-up there were no complaints of neck pain, no radiologic signs of implant failure were found, and a bony union between C1 and C2 was present in all patients.Conclusion Dorsal cervical C1–C2 fusion using C1 lateral mass screws, C2 lamina screws, and interarcual bone graft are less common techniques, although they can be used safely and demonstrated excellent clinical results with regard to pain relief and a high fusion rate. The technique is an ideal alternative when other techniques are not safe for anatomical reasons.
Keywords: lamina screws; lateral mass screws; posterior cervical fusion; atlantoaxial instability